Empowering Cadres in Reducing Stress Levels in the Elderly During the Covid 19 Pandemic - Rosmin Ilham; Andi Nur Aina Sudirman; Nur Mawaddah Polihito; Muhammad Rizky Mardan Maku; Azizah Oktavina Pontoh; Novita Hasan (Pusat Studi Pembangunan dan Pemberdayaan, 2022)
The increase in the transmission of the Covid-19 disease causes its own anxiety for the elderly. Various efforts have been made to reduce the anxiety of the elderly, one of which is by increasing the spiritual aspect. The lack of spiritual aspects causes the elderly to be pessimistic and unable to surrender the problems they face to Allah SWT. This service activity aims to provide counseling about empowering cadres in reducing the stress level of the elderly during the covid 19 pandemic by means of deep breathing relaxation techniques and istighfar properly and correctly to deal with stress in the elderly. The activity was carried out by involving the Cadre and Community of Talumelito Village, Telaga Biru District, Gorontalo Regency, to be given counseling by the service team and the students involved. This activity involved 2 service lecturers and 9 volunteer students from UM-Gorontalo. The service activity was carried out on February 23, 2022 at the Talumelito Village Hall, District Telaga Biru Gorontalo Regency. The results obtained by the community are able to know stress management by means of deep breathing relaxation techniques and Istighfar